Origin of organic matter and paleo-sedimentary environment reconstruction of the Triassic oil shale in Tongchuan City, southern Ordos Basin (China). (15th November 2017) - Li, Delu; Li, Rongxi; Zhu, Zengwu; Wu, Xiaoli; Cheng, Jinghua; Liu, Futian; Zhao, Bangsheng
Abstract: Owing to the lack of conventional oil resources, oil shale from the Triassic Yanchang Formation in the southern Ordos Basin has attracted unprecedented attention. The origin of organic matter and the paleo-sedimentary environment of oil shale are discussed. Based on the results of total organic carbon (TOC), total sulfur (TS), rock pyrolysis, organic elements, vitrinite reflectance (Ro), biomarkers, major elements, and trace elements of oil shale from Yishicun Profile, Tongchuan City. The oil shale from the Chang 7 sub-unit has high TOC (0.29–24.68%) and low TS content (0.13–0.61%), exhibiting middle-grade criterion and extra-low sulfur quality. The Ro, together with discrimination diagrams of C2 9steraneββ/(ββ + αα)-αααC2 9sterane20 S/(20 S + 20 R) and OEP-CPI, suggests that the oil shale has reached maturity. C27 − C29 regular steranes distribution, (C19 + C20 tricyclic terpane)/C23 tricyclic terpane, and C23 tricyclic terpane/(C23 tricyclic terpane + C30 hopane) all indicate that the parent materials of the organic matter in the oil shale are algae, phytoplankton, and terrestrial plants. The Pr/Ph, V/Cr, V/(V + Ni), U/Th, δU, and TOC-TS-TFe2 O3 ternary diagrams indicate that oil shale mainly deposits in reducing environment with a relatively poor preservation conditions. TS content, gammacerane/αβ-C30 hopane, gammacerane/0.5C31 αβ(22 R + 22 S), and Equivalent Boron accurately explain that marine transgression did not occur and the paleosalinity of the lake indicates predominantly fresh water. The paleoproductivity of the lake during oil shale sedimentation is very high in terms of U and Mo concentrations and Ba/Al ratio. After quantitative calculation, the lake is classified as an extremely eutrophic lake. The water depth of oil shale sedimentation varies from 26.00 to 108.6 m, indicating a semi deep- deep lake.